Explaining the Concept of Islamic Simplicity in Architecture (Through Examples of Contemporary Mosque Architecture) - Mohammad Hossein Mirza Kouchak Khoshnevis; Akabar Haji Ebrahim Zargar; Mansoureh Tahbaz (صفه)
Simplicity in architecture has always been considered a discission of utmost importance in architectural circles. In this article, simplicity in architecture is explained in both its material and spiritual aspects. In the material point of view, simplicity is summed up as a means to achieve the desired material end in the architectural structure. In the spiritual perspective, though, in addition to the material aspect, the architectural work must also establish simplicity in order to achieve a spiritual end. The conformity of the material to the spiritual end in different religious teachings is interpreted as asceticism (Zuhd), whose qualities, levels and limits can vary depending on the worldview of each, and in turn it affects their architecture. Therefore, the main question of this research is what constitutes the Islamic simplicity and how it is manifested?The hypothesis cum answer to this question, does not consider Islamic simplicity as the elimination of ornaments, patterns, colours and signs from the architectural work. In line with this, a qualitative research is conducted based on descriptive-analytical method, in which the material aspect of simplicity is studied in architectural sources, whilst its spiritual aspects is sought in moral and religious sources. The results showed that contrary to the monastic approach that rejects any desire for the world, the Islamic simplicity considers true asceticism as based on moderation and creating the greatest divine closeness to the desire for the world. Therefore, an architecture based on Islamic simplicity is multifaceted, all of which intending to bring about a nearness to God. Islamic simplicity in mosque architecture was then studied as a manifestation of Islamic art. The results showed that the concept of simplicity in the architecture of contemporary mosques, both in explaining the material end and its adaptation to the spiritual end, is not consistent with the Islamic simplicity explained in this study. This means that some mosques do not have their most desirable material condition and do not use true Islamic asceticism in explaining the spiritual end.